Penerapan Pendekatan Revolusi Pemasaran dan Revolusi Produksi dalam Membantu Perkembangan Masyarakat Menuju Industri 5.0 - Adrian Hartanto Darma Sanputra (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Industry 5.0 emerges as the next evolution in industrial development accelerated by digital innovation, artificial intelligence (AI), the Internet of Things (IoT), and quantum computing. This transformation not only affects technological aspects but also has a profound impact on how society interacts with products, services, and its environment. This article describes how the approaches of marketing revolution and production revolution can be employed as tools to support societal development in facing Industry 5.0. The research aims to explore the roles of innovative marketing strategies and production efficiency in shaping the future of society in the era of Industry 5.0. As a follow-up to these developments, UMKM 5.0 was launched on Friday 20 Oktober 2023, as one of the efforts to uplift micro, small, and medium-sized enterprises (MSMEs) by leveraging internet technology. One of the initiatives involves providing training to MSME entrepreneurs to enable them to expand their businesses through the internet and the utilization of artificial intelligence.